STRATEGI PENGEMBANGAN SUMBER DAYA MANUSIA DALAM MENINGKATKAN DAYA SAING ORGANISASI - Asnan, Asnan; Sulamiatin, Sulamiatin (POLITEKNIK LP3I JAKARTA, 2026)
Human resource development plays an important role in improving organizational performance and competitiveness in an increasingly competitive global environment. Organizations are required to have competent, innovative, and adaptive human resources to respond to dynamic business changes. This study aims to analyze the concept of human resource development, examine strategies for developing human resources, and identify their role in enhancing organizational competitiveness. This research uses a qualitative approach with a literature review method. The data used are secondary data obtained from textbooks, scientific journal articles, and research reports related to the topic. Data collection was carried out through documentation studies, while the analysis employed descriptive qualitative techniques by reviewing and synthesizing relevant theories. The results show that human resource development contributes to improving employee competence, productivity, organizational innovation, and employee commitment. Strategies such as training programs, career development, performance management systems, and strengthening organizational culture can support the development process. Effective implementation of these strategies can improve product and service quality, increase operational efficiency, and enhance customer satisfaction. Therefore, human resource development becomes an important factor in creating sustainable organizational competitiveness.